Boundary-Value problems for systems of integro-differential equations with Degenerate Kernel - Boichuk, О. A.; Krivosheya, S. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using methods of the theory of generalized inverse matrices, we establish a criterion of solvability and study the structure of the set of solutions of a general linear Noether boundary-value problem for systems of integro-differential equations of Fredholm type with degenerate kernel.